Pengembangan Media Pembelajaran Interaktif Robot Wampi untuk Peserta Didik Disabilitas Intelektual - Fudak Winduko; Endang Pudjiastuti Sartinah; Wagino Wagino (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to develop an interactive digital learning media called Robot WAMPI (WhatsApp and Interactive Learning Media), specifically designed to improve early reading skills among students with intellectual disabilities. Using an R&D approach with the ADDIE model. This study involved six students with intellectual disabilities at the Banjarsari Special Needs School (SLB) who were selected purposively. Data were collected through questionnaires and tests, then analyzed using a Likert scale and the Wilcoxon test. Data sources came from media experts, material experts, teachers, and students. Validation by media and content experts showed high feasibility, with 98% and 97% validity scores, respectively. A practicality test by teachers yielded a score of 92%, indicating the media is user-friendly, engaging, and appropriate for the students’ characteristics. Furthermore, effectiveness testing significantly improved students’ early reading abilities. These findings confirm that Robot WAMPI is a valid, practical, and effective innovative learning solution for inclusive education in special schools(SLB).